The Comparison of TGF-β Levels in Post Pulmonary Tuberculosis Patients with and Without Smoking History in Haji Adam Malik General Hospital Medan - Shilvanna Litania; Amira P. Tarigan; Fajrinur Syarani (Jurnal Respirologi Indonesia, 2020)
Backgrounds: Pulmonary tuberculosis (TB) and smoking related disease such as chronic obstructive of lung disease (COPD) are major health problem around the world, particularly in developing countries such as Indonesia. Chronic airway obstruction as impact of TB may results during or after completion of TB treatment. Transforming growth factor beta (TGF-β) is a cytokine which contributes to fibro genesis in post-TB treatment. The aim of this study was to compare the TGF-β in post-TB patients with and without smoking history. Methods: This was an analytic study with cross sectional design, conducted from October 2016 to February 2017 in RSUP H. Adam Malik Medan. All subjects had recovered from TB, confirmed by clinical, radiological and bacteriological examination. Smoking history of the subjects was assessed using Brinkman Index. The TGF-β measurement was performed using venous blood sample processed through Enzyme Link Immunosorbent Assay (ELISA) by means of TGF-β kit. Results: This study included post-pulmonary TB patients, of which 26 subjects were smokers and 25 were non-smokers, consisted of 31 males and 20 females. The mean TGF-β level of all samples was 6690.5±4913.4 mg/ml. The mean TGF-β level in smokers was 6621.5±4856.7 mg/ml, while in non-smokers 6762.2±5071 mg/ml. Statistical analysis using Mann-Whitney test revealed that there were no significant differences of TGF-β level in smokers and non-smokers among post-pulmonary TB patients (P=0.618). Conclusions: There were no significant differences of TGF-β level in smokers and non-smokers among post-pulmonary TB patients. (J Respir Indo. 2020; 40(3): 139-43)